Breaking through the Justice Wall for the Underprivileged People In Criminal Cases - Nurtresna, Robby; Mabsuti, Mabsuti; Hidayat, Syahril; Putri, Nabila (Fakultas Syariah INSURI Ponorogo, 2025)
The motto “Justitiae Non Est Neganda, Non Differenda” (